2010
DOI: 10.1039/b914911b
|View full text |Cite
|
Sign up to set email alerts
|

Individual swollen starch granules under mechanical stress: evidence for deformation and volume loss

Abstract: International audienceThe behaviour of the individual swollen-in-water starch granule (modified waxy maize and potato) under shear stress was studied using a counter-rotating rheo-optical set-up. It was shown that the granules strongly deform under flow and eject solvent, which leads to a loss of volume. The possibility of using rheo-optics to determine the shear modulus of a single granule shear modulus was demonstrated. The difference between the two starches in the amount of solvent ejected was qualitativel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(7 citation statements)
references
References 22 publications
1
6
0
Order By: Relevance
“…Potato starch granules have an oval shape, corn and rice starch granules have a polyhedral shape, and wheat starch granules have a lenticular shape. Their general appearance is similar to that previously mentioned by other researchers [8,14,15,16]. The micrographs point to different size distributions, as confirmed by laser diffraction measurements.…”
Section: Resultssupporting
confidence: 89%
“…Potato starch granules have an oval shape, corn and rice starch granules have a polyhedral shape, and wheat starch granules have a lenticular shape. Their general appearance is similar to that previously mentioned by other researchers [8,14,15,16]. The micrographs point to different size distributions, as confirmed by laser diffraction measurements.…”
Section: Resultssupporting
confidence: 89%
“…In excess water, the shear modulus of swollen potato starch granules was a few hundred Pa (1.5 kPa at most) (Desse, et al, 2010). The work of Carrington, et al ( 1998) andFisher, et al ( 1997) was devoted solely to the identification of Young's modulus for swollen potato starch.…”
Section: At or Close To Ambient Temperaturementioning
confidence: 99%
“…Examples are starch concentration, temperature, shearing, and the exact composition of the starch in question, for example in terms of amylase/amylopectin ratio and lipid content . It has recently been shown that stresses as small as 1 kPa affect the volume of swollen starch granules .…”
Section: Introductionmentioning
confidence: 99%